Appraisal on Editorial Texts Related To Covid-19 in Newspaper in Dairi - Mia Fiona Simanjorang; Amrin Saragih; Thyrhaya Zein (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
This thesis aims to analyze the type and realization of Appraisal in the analysis of the content of the editorial texts of Dairi newspapers to find out the comparisons in each electronic newspaper by applying the three elements of Appraisal (attitude, positioning, and graduation). This research applies descriptive qualitative by using interactive model and document study as data collection. The data sources of this research are 20 phenomenal news texts from four different electronic newspapers and the data used in carrying out this research are the words, clauses contained in the text of the electronic newspaper. From the results of the analysis, it was found that the Appraisal contained in the editorial text of the regional electronic newspaper consisted of the engagement category with 97 clauses (29%), the judgment category with 94 clauses (28%), the appreciation category with 62 clauses (18%), the graduation category as much as 61 clauses (18%), and the last is the Affect category with 23 clauses (7%). Based on these findings, the subsystem that dominates the news text is the engagement subsystem.